1991
DOI: 10.2337/diab.40.4.499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Insulin and Amino Acids on Leg Protein Turnover in IDDM Patients

Abstract: To determine whether the responses of muscle protein metabolism to insulin and amino acids in patients with insulin-dependent diabetes mellitus (IDDM) were different from those in nondiabetic subjects, leg tissue kinetics of [15N]phenylalanine and [1-13C]leucine and its metabolites were measured in eight insulin-withdrawn IDDM patients and eight nondiabetic subjects during basal insulinemia and during infusion of insulin (0.29 nmol.min-1.m-2). The diabetic patients were studied in the absence of amino acids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
1
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 41 publications
0
23
1
1
Order By: Relevance
“…It is noteworthy that in these women, protein turnover was normalized by insulin treatment, but fasting and postprandial glutamate levels remained elevated despite the satisfactory glycemic control. There is clear evidence of altered protein metabolism also in T1D [176][177][178][179][180]. In T1D, insulin deficiency increases protein breakdown and the associated hyperglucagonemia accelerates protein catabolism [181].…”
Section: Plasma Glutamate Levels In Different Pathologic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that in these women, protein turnover was normalized by insulin treatment, but fasting and postprandial glutamate levels remained elevated despite the satisfactory glycemic control. There is clear evidence of altered protein metabolism also in T1D [176][177][178][179][180]. In T1D, insulin deficiency increases protein breakdown and the associated hyperglucagonemia accelerates protein catabolism [181].…”
Section: Plasma Glutamate Levels In Different Pathologic Conditionsmentioning
confidence: 99%
“…Acta Diabetol (2012) 49:[167][168][169][170][171][172][173][174][175][176][177][178][179][180][181][182][183] …”
unclassified
“…Sir William Osler, almost a 100 years ago, described the disease in terms of "progressive emaciation," involving massive urinary losses of both glucose and urea in diabetic patients (2). Insulin treatment not only improves control of glucose levels but also has a profound effect on protein metabolism, correcting increased urinary losses of nitrogen and increasing whole-body protein accretion, as indicated by whole-body potassium measurements (3)(4)(5)(6). It remains to be clearly defined whether insulin d e fic i e n c y, per se, is the cause of the catabolic state that occurs in poorly controlled type 1 diabetes.…”
mentioning
confidence: 96%
“…In vitro evidence indicates that insulin decreases skeletal muscle protein breakdown (2,22,24,31) and increases muscle protein synthesis (2,22,23,33,35). In humans, systemic insulin administration inhibits muscle protein breakdown in patients with T1DM (6,8,30,34) and in healthy subjects (13,29) but not confirmed by all studies (38). Systemic insulin administration causes hypoaminoacidemia, which may potentially affect muscle protein kinetics, since it has been shown that amino acids (AA) play a key regulatory role on insulin effect on protein synthesis and breakdown (16,21,27).…”
mentioning
confidence: 97%